GREEN URBANISM: THE ROLE OF SUSTAINABLE PUBLIC SPACES IN CLIMATE-RESILIENT CITY PLANNING - Hamidova Mohigul Hayotovna,; Vohidov Shakhzod Kenjayevich, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: As cities face increasing threats from climate change, sustainable urban planning has become essential for long-term resilience. This article explores the role of green public spaces—parks, green corridors, bioswales, and urban forests—in enhancing the ecological, social, and thermal performance of cities. Using global examples and referencing case studies from Central Asia, particularly Uzbekistan, the paper argues that green urbanism is not merely aesthetic but a critical infrastructure strategy. The study concludes that integrating sustainable public spaces into the urban fabric mitigates urban heat island effects, improves air quality, and enhances urban well-being, especially in developing cities with extreme climates.